Magic tree house Lions on the loose - Osborne, Mary Pope (Red Fox London, 2009)
Whisked away to the plains of Africa, Jack and Annie can't believe how many wild animals they see! When a pride of lions crosses their path, they'll need a clever plan of escape. Can Jack and Annie get back to the tree house without becoming lunch for the lions?